Predicting self-oxidation of coals and coal/biomass blends using thermal and optical methods - Avila, Claudio (2012)
Self-oxidation and spontaneous combustion of coals is a problem of global concern. There are social, economic and environmental costs associated with this phenomenon and major incidents can, in extreme cases, lead to human casualties. More often however, damage is made to commercial facilities, the calorific value of the fuel is reduced and substantial release of noxious gases, particulate matter and CO2 may contribute to local and international pollution levels. This problem is not only restricted to coals, it also affects other carbonaceous materials such as biomass and potentially coal-biomass blends. A considerable amount of literature has been published, and whilst the causes are relatively well understood, the existing methods for predicting spontaneous combustion are not reliable enough for scientists or the coal industry. This research focuses on understanding the oxidation characteristics of coal, biomass and coal-biomass blends at low temperatures, with the aim of defining a set of experimental test procedures to identify coal and biomass propensity to spontaneously combust. Based on a comprehensive literature survey, two main research areas were identified as feasible sources of information to detect prone coals: microscopy and thermal analysis. Considering these, an extensive experimental program was carried out using 42 coals (including at least three well known samples prone to spontaneous combustion), 10 different biomass types, and a number of coal-biomass blends, including diverse particle and sample sizes, at different stages of the oxidation process. Initially, pulverized coal samples (size <106µm) were subjected to thermogravimetric and calorimetric tests (small sample size), and differential thermal analysis (large sample size) using a large scale reactor. From these tests, the link between the weight loss/gain of the samples and the reactivity at low temperature was confirmed, developing successfully two thermogravimetric tests to identify high risk samples. Afterwards, textural features of thermally altered coal samples (light reflectance and particle morphology) were studied by means of combined petrographic and image analysis techniques. Results showed that particle reflectance and textural changes depend on oxidation temperature, which are linked to the spontaneous combustion potential. Based on these results, two tests were proposed by comparing light reflectance before and after a slow oxidation, quantifying the formation of morphotypes associated with highly reactive samples. A similar approach was used to study biomass and coal-biomass blends, focusing on the quantification of intrinsic reactivity and particle morphology by TGA and optical microscopy. For raw and char biomass particles, results showed a significant correlation between the optical and reactivity properties. Additionally, several new morphotypes were identified from biomass char samples. These characteristics were associated with the thermal behaviour of large samples, although these results did not suggest any distinctive indicator to identify samples prone to self-heat, concluding that the low temperature oxidation of biomass is a completely different phenomenon to that experienced by coals. In the case of coal-biomass blends, the most relevant finding was a synergetic effect observed for the ignition temperature, which was always lower than the ignition temperature of the individual components. This finding has not been described in literature before, and further work is necessary in order to investigate this interaction in greater depth. Finally, a set of standardised procedures to assess the reactive properties of these materials has also been proposed.